2021
DOI: 10.1186/s12886-021-02001-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial using cyclopentolate and tropicamide to compare cycloplegic refraction in Chinese young adults with dark irises

Abstract: Background To evaluate the necessity of cycloplegia for epidemiological studies of refraction in Chinese young adults (aged 17–22 years) with dark irises, and to compare the cycloplegic effects of 1% cyclopentolate and 0.5% tropicamide in them. Methods A total of 300 young adults (108 males and 192 females) aged 17 to 22 years (mean 19.03 ± 1.01) were recruited from Tianjin Medical University from November 2019 to January 2020. Participants were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…This was also the first time anyone has deeply investigated the participants’ attitudes toward tele-controlled subjective refraction. In our cross-sectional study, we found no statistically significant differences between traditional subjective refraction and tele-controlled subjective refraction for any parameters, and the 95% limits of agreement between the 2 methods of refraction in the S (±0.42 D), C (±0.39 D), and SE (±0.36 D) were both similar to a previous study on reproducibility of subjective refraction (±0.44 D 16 for S, ±0.31 D 17 for C, and ±0.37 D to ±0.56 D 18 21 for SE). Researchers generally agree that the variation of refractive error should be at least ±0.50 D and consider this to be the minimum significant shift in a refractive state.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was also the first time anyone has deeply investigated the participants’ attitudes toward tele-controlled subjective refraction. In our cross-sectional study, we found no statistically significant differences between traditional subjective refraction and tele-controlled subjective refraction for any parameters, and the 95% limits of agreement between the 2 methods of refraction in the S (±0.42 D), C (±0.39 D), and SE (±0.36 D) were both similar to a previous study on reproducibility of subjective refraction (±0.44 D 16 for S, ±0.31 D 17 for C, and ±0.37 D to ±0.56 D 18 21 for SE). Researchers generally agree that the variation of refractive error should be at least ±0.50 D and consider this to be the minimum significant shift in a refractive state.…”
Section: Discussionsupporting
confidence: 88%
“…First, all subjective refraction was conducted without cycloplegia. As observed by Pei et al, 17 cycloplegic measurements are generally more positive or less negative than refractions without cycloplegia. Although enough fogging and standardized operations were performed to minimize the influences induced by accommodation, 31 this may not be enough for individuals with hyperopia or under the age of 10 years.…”
Section: Discussionmentioning
confidence: 55%
“…For other children, cycloplegia in our study was obtained by tropicamide instead, considering some children's photophobia and rejections from parents. However, as a recent prospective observational study shows similar effects in producing cycloplegia using tropicamide and cyclopentolate in Chinese young people, 31 the SER of children who received tropicamide may be overestimated. Thirdly, previous studies indicated that axial elongation usually occurred concurrently with loss of lens power in children.…”
Section: Discussionmentioning
confidence: 97%
“…At baseline, cycloplegic autorefraction was performed 30 min after three instillations of tropicamide 1% drops, 5 min apart. 10 Care was taken to see that the pupils were dilated to at least 6 mm and that no pupillary reflex was present post dilatation. Automated refraction was measured using the Nidek ARK-1 autorefractor (nidek -intl.com).…”
Section: Methodsmentioning
confidence: 99%